Description of Morphological Abnormalities in Rhinella arenarum (ANURA: BUFONIDAE) - Chilote, P.D.; Bozzolo, L.E.; Gutierrez, F.R.; Moreno, L.E. (Journal of Morphological Sciences, 2018)
The rise of anatomical abnormalities in anurans over recent years has increased the interest in producing more and better information about the abnormalities observed in specimens within natural environments that are currently being altered. The aim of this work was to identify and describe la osseous abnormalities found in Rhinella arenarum. Four samplings were conducted between March 2009 and February 2010 in the Claro river, located in San Francisco in the Ayacucho Department in the province of San Luis. Specimens of R. arenarum with visible abnormalities were observed and collected manually. They were euthanized in the laboratory, preserved in 10% formaldehyde, and stored in the Herpetological Collection Unit of the National University of San Luis (CH-UNSL). The Alizarin-Alzian technique was also applied to the specimens. Photographs of the abnormalities were taken, and observations were made with a stereoscopic microscope. The following abnormalities were identified and described: femur ectromelia, tibial and fibular ectromelia, ectrodactylia and brachydactyly. Further work could focus on determining the causes of the abnormalities observed in this species, conducting an integrated study, and attempting to link this with the worldwide phenomenon of amphibious declination.
Keywords: abnormalities; rhinella arenarum; brachydactyly; ectrodactylia; ectromelia